Uji Aktivitas Antibakteri Kombinasi Minyak Atsiri Biji Ketumbar (Coriandrum sativum L.) dan Gentamisin terhadap Staphylococcus epidermidis - Bawon Triatmoko; Huda Almuttaqin; Dewi Dianasari (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Gentamicin is one of the antibiotics from the aminoglycoside group used for the treatment of infections. Gentamicin has side effect such as permanent ototoxicity and reversible nephrotoxicity. It was necessary to reduce these effects by combining antibiotic with natural ingredients, one of those is coriander seeds essential oil. Combination therapy is done to reduce the potential side effects, and increase antibacterial efficacy. Antibacterial activity test were conducted to measure the MIC values of gentamicin, essential oils of coriander seeds, and combination of both. Based on the antibacterial activity test, MIC value of gentamicin was 4 µg/mL, coriander seed essential oil was 50 µg/mL and MIC combination of gentamicin and essential oil of coriander seeds were 0.5 µg/mL and 50 µg/mL. The FIC Index value obtained was 1.125 meaning that the combination effect was indifferent. Indifferent combination effect means the use of a combination of coriander seeds essential oil and gentamicin as antibacterial was not better than the single use. Keywords: coriander, essential oil, antibacterial, FIC Index, S. epidermidis